Analysis of Chinese Language Learning Motivation and Cultural Preservation of Chinese Indonesian High School Students - Sugiato Lim (Humaniora, 2014)
This paper analyzes Chinese Indonesian high school students, their language and cultural preservation, and also their motivation to keep learning Chinese. By related survey, this paper tries to find out more about how far the young generation of Chinese Indonesian retains their language and culture as well as their motivation tolearn Chinese. The contents particularly concern the subjects of Chinese learning experience, motivation, mother-tongue language and religion backgrounds, Chinese festivals and customs and other topics. Survey results indicate that the post-90s young generation of Chinese Indonesian, in terms of the language recognition,has generally assimilated culture in Indonesia. In addition, in cultural preservation aspect, the students still retain several Chinese major folk customs.